Travelling wave solutions of the reaction-diffusion mathematical model of glioblastoma growth: An Abel equation based approach - Tiberiu Harko; Man Kwong Mak (Mathematical Biosciences and Engineering)
We consider quasi-stationary (travelling wave type) solutions to a nonlinearreaction-diffusion equation with arbitrary, autonomous coefficients,describing the evolution of glioblastomas, aggressive primary brain tumorsthat are characterized by extensive infiltration into the brain and arehighly resistant to treatment. The second order nonlinear equationdescribing the glioblastoma growth through travelling waves can be reduced to a first order Abel typeequation. By using the integrability conditions for the Abel equationseveral classes of exact travelling wave solutions of the general reaction-diffusion equation that describes glioblastoma growth are obtained, corresponding to different forms of the product of the diffusion and reaction functions. The solutions are obtained by using the Chiellini lemma and the Lemke transformation, respectively, and the corresponding equations represent generalizations of the classical Fisher--Kolmogorov equation. The biological implications of two classes of solutions are also investigated by using both numerical and semi-analytical methods for realistic values of the biological parameters.